A Nanosheets‐on‐Channel Architecture Constructed from MoS2 and CMK‐3 for High‐Capacity and Long‐Cycle‐Life Lithium Storage. Issue 17 (24th July 2014) - Xu, Xin; Fan, Zhaoyang; Yu, Xinyao; Ding, Shujiang; Yu, Demei; Lou, Xiong Wen (David)
<x xml:space="preserve">Abstract</x> A unique hybrid nanostructure of ultrathin MoS2 nanosheets on CMK‐3 is designed and fabricated as an anode material for lithium‐ion batteries. With advantages of the nanosheets‐on‐channel architecture, the MoS2@CMK‐3 electrode is able to deliver a high discharge capacity of 934 mAh g−1 even after 150 cycles at a current density of 400 mA g−1. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>